Пожалуйста-пожалуйста,
на вас надежда:







1. Sin (arcsin  \frac{2}{7} ) =
2. Cos (arcsin  \frac{1}{5} ) =
3. tg (arcsin  \frac{1}{4} ) =
4. tg (arcsin  \frac{4}{5} ) =
5. tg (arctg 7) =
6. ctg (arctg  \frac{1}{3} ) =

2

Ответы и объяснения

2014-03-13T01:12:24+04:00
1)3sin^2(x)+13sinx*cosx+12cos^2(x)=0;поделим на cos^2(x),не равное нулю.
3tg^2(x)+13tgx+12=0
tgx=t
3t^2+13t+12=0
t=(-13+-5)/6
t1=-8/6=-4/3
t2=-3
tgx=-4/3
x=arctg(-4/3)+Пn,n принадлежит Z.
tgx=-3
x=arctg(-3)+Пn,n принадлежит Z.
2)5tgx-6ctgx+7=0
5tgx-(6/tgx)+7=0
tgx=t
5t-(6/t)+7=0
5t^2+7t-6=0
t=(-7+-13)/10
t1=6/10=3/5
t2=-2
tgx=3/5
x=arctg(3/5)+Пn,n принадлежит Z.
tgx=-2
x=arctg(-2)+Пn,n принадлежит Z.
3)sin^2(x)+2sin2x=5cos^2(x)
sin^2(x)+4sinx*cosx-5cos^2(x)=0, делим на cos^2(x),не равное нулю.
tg^2(x)+4tgx-5=0
tgx=t
t^2+4t-5=0
t1=-5
t2=1
tgx=1
x=П/4+Пn,n принадлежит Z.
tgx=-5
x=arctg(-5)+Пn,n принадлежит Z.
4)13sin2x-3cos2x=-13
26sinx*cosx-3*(cos^2(x)-sin^2(x))=-13*(cos^2(x)+sin^2(x))
26sinx*cosx-3cos^2(x)+3sin^2(x)+13cos^2(x)+13sin^(x)=0
10cos^2(x)+26sinx*cosx+16sin^2(x)=0,снова делим на cos^2(x),не равное нулю.
16tg^2(x)+26tgx+10=0
tgx=t
8t^2+13t+5=0
t1=-1
t2=-5/8
tgx=-1
x=-П/4+Пn,n принадлежит Z.
tgx=-5/8
x=arctg(-5/8)+Пn,n принадлежит Z.
  • Участник Знаний
2014-03-13T01:38:36+04:00
1.(2/7
2.√1-1/25=√24/25=2√6/5
3.1/4:√1-1/16=1/4*4/√15=√15/15
4.4/5:√1-16/25=4/5:3/5=4/3
5.7
6.1:1/3=3